2021
DOI: 10.1002/oby.23244
|View full text |Cite
|
Sign up to set email alerts
|

Salmon peptides limit obesity‐associated metabolic disorders by modulating a gut‐liver axis in vitamin D‐deficient mice

Abstract: Objective This study investigated the effects of a low‐dose salmon peptide fraction (SPF) and vitamin D3 (VitD3) in obese and VitD3‐deficient mice at risk of metabolic syndrome (MetS). Methods Obese and VitD3‐deficient low‐density lipoprotein receptor (LDLr)−/−/apolipoprotein B100 (ApoB)100/100 mice were treated with high‐fat high‐sucrose diets, with 25% of dietary proteins replaced by SPF or a nonfish protein mix (MP). The SPF and MP groups received a VitD3‐deficient diet or a supplementation of 15,000 IU of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Thus, there is no recommendation for vitamin K level dosing in these patients. Vitamin D is not only crucial for bone integrity and the prevention of osteoporosis but also modulates intestinal permeability and inflammatory response to pathogens [ 48 ]. Therefore, it can be supplemented for patients with ALF with low levels of vitamin D [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is no recommendation for vitamin K level dosing in these patients. Vitamin D is not only crucial for bone integrity and the prevention of osteoporosis but also modulates intestinal permeability and inflammatory response to pathogens [ 48 ]. Therefore, it can be supplemented for patients with ALF with low levels of vitamin D [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Frisingicoccus , which was reported to be enriched in the gut of pigs by supplementing zinc in the diet ( Rattigan et al, 2020 ), was specifically enriched in M6, M7, and M8 groups compared to the M9. Mogibacterium , which might help to attenuate ileal inflammation and would be enriched in the human gut with vitamin D3 ingestion ( Valle et al, 2021 ), was specifically enriched in M10, M11 and M12 groups compare to M9. All the samples of the juvenile SC in this study were collected each month from three juvenile SC that lived in the same cage from 5 months old to 12 months old and they were fed the same diet, therefore the different genera found in the samples collected from different months were probably caused by the age of the juvenile SC.…”
Section: Discussionmentioning
confidence: 99%
“…Faghih et al [ 106 ] reported that diet of a daily 500 kcal deficit with daily 500–600 mg CAL (1), a daily 500 kcal deficit with daily 800 mg CAL (2), a daily 500 kcal deficit with three servings of low-fat milk (3), and a daily 500 kcal deficit with three portions of CAL-fortified soy milk (4), resulted in decreased body weight and BMI in all groups of healthy, overweight, or obese premenopausal women aged 20–50 years. Valle et al [ 103 ] showed that supplementation of salmon peptide fraction (25% of protein) and VD (15,000 IU/kg of diet) aided in maintaining metabolic syndrome via gut–liver axis by controlling hepatic and gut inflammation (increasing Mogibacterium and Muribaculaceae ) in mice fed with high-fat and high-sucrose diets containing VD (25 IU/kg of diet). Sharifan et al [ 108 ] observed a correlation between fortified dairy products containing VD 3 (1500 IU) and anthropometric indices, glucose homeostasis, and lipid profiles in adults (30–50 years old) with abdominal obesity.…”
Section: Interrelationship Of Vd–cal In Obesity and Its Disease Statesmentioning
confidence: 99%
“…There is also data showing harmful effects caused by consuming these nutrients alone or in combination [ 132 ]. However, prior studies on animal models [ 98 , 99 , 100 , 101 , 102 , 103 ] and humans largely [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ] recommend the use of VD–CAL as potential therapeutic agents for the management of obesity.…”
Section: Limitationsmentioning
confidence: 99%